ESTIMATING THE FACTORS INFLUENCING CAT FISH FARMERS’ INTEREST IN FISH PRODUCTION IN ILORIN, KWARA STATE - Jatto, N.A.; Alkali, A.; Galadima, Z. I.; Gunu, U.I.; Maikasuwa, M.A. (European Scientific Journal, ESJ, 2013)
Inadequate information on the determinant of cat fish farmers’ interest in fish production often limits the opportunity to predict the level of preference for fish production. Towards this end a study has been conducted in Ilorin, Kwara state capital to estimate the factors influencing cat fish farmers’ interest in fish production. A stratified random sampling technique was adopted in selecting a total sample size of 120 farmers, out of which 60 were fish farmers and the other 60 were non fish farmers selected from the list of all farmers association of Nigeria, Ilorin branch. A structured questionnaire was administered to obtain the information needed from the sampled farmers. Data analyses were done using descriptive statistics and binary Logit regression. The result revealed that year of education, labour, Farm size, income, participation in cooperative society are the significant factors contributing to cat fish farmers’ interest in fish production. The study concluded that participation in cooperative society is the major factor influencing the interest of cat fish farmers’ interest in fish production. The study recommends that cooperatives societies should be strengthened to encourage technical innovations and with timely availability of necessary inputs that can assist the fish farmers and government should influence by reducing the interest rates on credit so as to encourage and accelerate the transformation of fish industry as majority of the farmers find cooperative society as an avenue of borrowing.